In Defence of Democracy - Rovira i Virgili, Antoni (Universitat Rovira i Virgili, 2014)
In 1930, Antoni Rovira i Virgili published In Defence of Democracy, a book which is as relevant today as ever, given our current political and social circumstances. It reveals its author to be deeply acquainted with and full of insight into the political theory and philosophy of his time. In coming to the defence of democratic values at a time when autocratic styles of government had a growing appeal, Rovira i Virgili's intelligence and premonition are impressive. This book will surely appeal to anyone interested in politics and public life.